De novo formation of nucleoli in developing mouse embryos originating from enucleolated zygotes - Kyogoku, Hirohisa; Fulka, Josef; Wakayama, Teruhiko; Miyano, Takashi (Development (Cambridge, England), 2014)
The large, compact oocyte nucleoli, sometimes referred to as nucleolus precursor bodies (NPBs), are essential for embryonic development in mammals; in their absence, the oocytes complete maturation and can be fertilized, but no nucleoli are formed in the zygote or embryo, leading to developmental failure. It has been convincingly documented that zygotes inherit the oocyte nucleolar material and form NPBs again in pronuclei. It is commonly accepted that during early embryonic development, the original compact zygote NPBs gradually transform into reticulated nucleoli of somatic cells. Here, we show that zygote NPBs are not required for embryonic and full-term development in the mouse. When NPBs were removed from late-stage zygotes by micromanipulation, the enucleolated zygotes developed to the blastocyst stage and, after transfer to recipients, live pups were obtained. We also describe de novo formation of nucleoli in developing embryos. After removal of NPBs from zygotes, they formed new nucleoli after several divisions. These results indicate that the zygote NPBs are not used in embryonic development and that the nucleoli in developing embryos originate from de novo synthesized materials.
Keywords: Mice, Inbred ICR; buňky NIH 3T3; zygota; NIH 3T3 Cells; Zygote; Embryo; těhotenství; Oocyte; buněčné dělení; myši inbrední C57BL; mužské pohlaví; buněčné jadérko; Cell Division; Mice; Nucleolus; Embryo Culture Techniques; mikromanipulace; Oocytes; ženské pohlaví; Cumulus Cells; zvířata; oocyty; přenos embrya; myši inbrední ICR; Pregnancy; Mice, Inbred DBA; kumulární buňky; myši; Mouse; kultivace embrya; Blastocyst; myši inbrední DBA; Cell Nucleolus; Embryo Transfer; Female; Micromanipulation; blastocysta; Mice, Inbred C57BL; Male; Animals